Application of Technology in Islamic Education Management: Strengthening Digital Ethics as a Strategy for Developing Student Morals in the Social Media Era: Penerapan Teknologi dalam Manajemen Pendidikan Islam: Penguatan Etika Digital sebagai Strategi Pembinaan Akhlak Siswa di Era Media Sosial - Dede Ilham; Mohamad Madum (Fakultas Tarbiyah Dan Ilmu Keguruan Institut Agama Islam An-Nawawi Purworejo, 2025)
The rapid development of social media has brought significant changes in student interaction patterns and behavior, including in moral and ethical aspects. The rampant misuse of digital media, such as hate speech, the spread of hoaxes, and the degradation of communication ethics, indicates a serious challenge for Islamic education in instilling the values ​​of akhlakul karimah (good morals). This study aims to analyze the role of strengthening digital ethics in Islamic education and strategies for fostering students' morals in the social media era. This study uses a qualitative approach with a literature study method, by reviewing various relevant literature sources, including books, journal articles, and educational policy documents. The results show that digital ethics is an integral part of Islamic education, serving as a normative foundation for guiding student behavior in the digital space. Islamic values ​​such as honesty, responsibility, communication etiquette, and moderation need to be systematically internalized in the learning process to shape students' character with noble character and wisdom in using social media. Furthermore, integrating digital ethics into the Islamic Religious Education curriculum is an important strategy in strengthening students' moral development to face the moral challenges of the digital era. This study concludes that Islamic education has a strategic role in building students' ethical awareness so that they are able to utilize social media positively, responsibly, and in line with Islamic values.